PENYESUAIAN HUKUM NASIONAL INDONESIA TERHADAP KONVENSI PBB ANTI-KEJAHATAN SIBER 2024: KAJIAN PUSTAKA TENTANG HARMONISASI UU ITE DAN KUHP UNTUK PENGUATAN PENANGANAN KEJAHATAN SIBER LINTAS NEGARA - Gunawan Widjaja (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
Cross-border cybercrime is on the rise and poses a serious threat to national and global security. In 2024, the United Nations adopted the Anti-Cybercrime Convention as an international legal instrument to regulate the criminalisation of cybercrime, cooperation mechanisms, and the protection of human rights in the handling of cybercrime. Indonesia, as a country with a high level of internet penetration, faces the challenge of adjusting its national laws to be in line with the provisions of the convention. This study uses a normative legal method with a legislative and comparative law approach to analyse the harmonisation of the Electronic Information and Transaction Law (EIT Law) and the Criminal Code (KUHP) with the 2024 UN Convention on Cybercrime. The results of the study show that adjustments to substantive and procedural rules, strengthening international cooperation mechanisms, and protecting human rights in the ITE Law and the Criminal Code are essential to improve the effectiveness of handling complex cross-border cybercrime. This harmonisation of national laws is key for Indonesia to strengthen its legal framework in facing the threat of cybercrime while playing an active role as part of the international legal order.